Identification and characterization of forced degradation products of lumateperone tosylate by LC-HRMS, GC-MS, NMR, and in silico toxicity prediction - Nehal Bhatt; Devendra Sonaje; Vijiaya Madhyanapu Golla; Rahul Khemchandani; Roshitha K. R; Arun Kumar Gupta; Gananadhamu Samanthula (Journal of Pharmaceutical and Biomedical Analysis Open)
This study presents a detailed forced degradation profiling of lumateperone under stress conditions to develop a stability-indicating method capable of separating degradation products (DP-1 to DP-11), followed by their identification and characterization using hyphenated analytical techniques. Significant degradation was observed under oxidative, acidic, alkaline, and photolytic conditions. Oxidative stress generated an intensely colored quinone derivative (DP-2) as a major degradation product along with DP-3, DP-4, and DP-6. Alkaline hydrolysis yielded N-dealkylated and hydroxylated species (DP-1, DP-4, DP-5) and also produced a volatile degradation product, DP-7. Photolytic stress resulted in DP-2 and DP-8, whereas neutral hydrolysis led to the formation of DP-1, DP-2, DP-4, and DP-7. Notably, acidic hydrolysis in hydrochloric acid triggered dimer degradation product (DP-9) and chlorinated positional isomers of lumateperone (DP-10 and DP-11). The chemical structures of DP-1 to DP-6 and DP-8 to DP-11 were proposed by liquid chromatography-high-resolution mass spectrometry (LC-HRMS). DP-7 was identified as 1-(4-Fluorophenyl)ethanol using gas chromatography-mass spectrometry (GC–MS). The major degradation product, DP-2, was isolated and further characterized by nuclear magnetic resonance (NMR). A few DPs shared structural features with previously reported metabolites, suggesting a resemblance between chemical degradation and metabolic processes. The developed method was validated in accordance with ICH Q2(R1), demonstrating excellent linearity (r² > 0.999), accuracy, precision, specificity, and robustness. In silico toxicity analysis using ADMET Predictor® flagged four DPs (DP-1, DP-2, DP-5, and DP-6) with mutagenic alerts and predicted additional hepatotoxic, cardiotoxic, and receptor-mediated risks.These findings support formulation and quality management of lumateperone.